Assessing anti‐SARS‐CoV‐2 cellular immunity in 571 vaccines by using an IFN‐γ release assay. Issue 12 (28th October 2022) - Wakui, Masatoshi; Uwamino, Yoshifumi; Yatabe, Yoko; Nakagawa, Terumichi; Sakai, Akiko; Kurafuji, Toshinobu; Shibata, Ayako; Tomita, Yukari; Noguchi, Masayo; Tanabe, Akiko; Arai, Tomoko; Ohno, Akemi; et al.
Abstract: Memory T cell responses have been analyzed only in small cohorts of COVID‐19 vaccines. Herein, we aimed to assess anti‐SARS‐CoV‐2 cellular immunity in a large cohort using QuantiFERON assays, which are IFN‐γ release assays (IGRAs) based on short‐term whole blood culture. The study included 571 individuals receiving the viral spike (S) protein‐expressing BNT162b2 mRNA vaccine. QuantiFERON assays revealed antigen‐specific IFN‐γ production in most individuals 8 weeks after the second dose. Simultaneous flow cytometric assays to detect T cells expressing activation‐induced markers (AIMs) performed for 28 randomly selected individuals provided data correlating with the QuantiFERON data. Simultaneous IFN‐γ enzyme‐linked immunospot and AIM assays for another subset of 31 individuals, based on short‐term peripheral blood mononuclear cell culture, also indicated a correlation between IFN‐γ production and AIM positivity. These observations indicated the acquisition of T cell memory responses and supported the usability of IGRAs to assess cellular immunity. The QuantiFERON results were weakly correlated with serum IgG titers against the receptor‐binding domain of the S protein and were associated with pre‐vaccination infection and adverse reactions after the second dose. The present study revealed cellular immunity after COVID‐19 vaccination, providing insights into the effects and adverse reactions of vaccination. Abstract : We assessed anti‐SARS‐CoV‐2 cellular immunity in 571 vaccinees by using an interferon‐γ release assay based on short‐term whole blood culture with simultaneous flow cytometric assays to detect activation‐induced marker expression of T cells for 28 randomly selected individuals. The present study revealed cellular immunity after COVID‐19 vaccination, providing insights into the effects and adverse reactions of vaccination.